Social representations in the interaction with students of the Inga tribes (2018)
Citizen competences as a transversal axis in education in Colombia have had a characteristic development within the pedagogical practices in the different educational levels. The purpose of the research was to understand the pedagogical practices and the social representations that emerge in the classroom and outside of it by teachers and university students belonging to the Inga tribe, around the development of Citizen Competencies. The research is part of the qualitative approach based on the hermeneutical ethnographic method, a valid tool for understanding the meanings given in a historical moment. Emerging categories are framed within the scope of the Citizen Competencies standards,coexistence and peace; participation and democratic responsibility and plurality, identity and assessment of differences, likewise, categories emerge in housing, roles in communication, work. Conclusion: education for life, the preservation of health and nature, is an emerging family associated with coexistence, communication, the transfer of knowledge and society in interaction with students of the Inga tribe.